Improving Recruitment Efficiency And Effectiveness Through AI And Automation: A Literature Review - Carolina, Sisi Yulisia; Putri, Ratih Lintang; Djangkaru, Ruth Riyani (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2025)
This study aims to explore the role of Artificial Intelligence (AI) and automation technologies in transforming modern recruitment processes. Through a systematic literature review, this study analyzes how advanced technologies can improve the efficiency and effectiveness of human resource management. The research method uses a literature study approach by collecting and analyzing 30 scientific articles from various academic databases between 2019-2024. The review results show that AI implementation in recruitment can optimize candidate selection processes, reduce subjective bias, and accelerate recruitment time by up to 60%. Automation technology has proven capable of comprehensively analyzing candidate profiles, processing application documents, and conducting pre-selection with high accuracy. This study concludes that the integration of AI and automation is a transformative strategy in modern recruitment management, providing a competitive advantage for organizations in recruiting quality talent. Recommendations for further research are to explore the ethical challenges and practical implementation of these technologies.